2015 11th Conference on Ph.D. Research in Microelectronics and Electronics (PRIME) 2015
DOI: 10.1109/prime.2015.7251412
|View full text |Cite
|
Sign up to set email alerts
|

Response of P(VDF-TrFE) sensor to force and temperature

Abstract: Responses of a tactile sensor to force (0 to 9 N) and temperature (15 to 47°C) are investigated. The sensor is based on ferroelectric polyvinylidene fluoride – trifluoroethylene (P(VDF-TrFE)) copolymer. The 2.5-µm-thick copolymer layer was sandwiched between aluminum and gold electrodes and the active sensing area was 25 mm2. The response of the sensor was measured in a form of capacitance recorded at 2 kHz. The capacitance was measured in a steady-state condition, i.e. after the force and temperature have sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[2,20,21]. The piezoelectric materials are unique as they allow us to measure dynamic touch or contact events and also enable multiple uses as sensors, actuators and energy harvesters [13,[22][23][24].…”
Section: A P(vdf-trfe) For Pressure/touch Sensorsmentioning
confidence: 99%
“…[2,20,21]. The piezoelectric materials are unique as they allow us to measure dynamic touch or contact events and also enable multiple uses as sensors, actuators and energy harvesters [13,[22][23][24].…”
Section: A P(vdf-trfe) For Pressure/touch Sensorsmentioning
confidence: 99%
“…Previously, we have reported that the capacitance of a ferroelectric P(VDF-TrFE) layer changes with force or temperature [20]. In addition, the ferroelectric co-polymer exhibits piezo-and pyroelectric properties.…”
Section: Introductionmentioning
confidence: 99%